Methyl (E)-3-(2-formylphenoxy)acrylate - Karthikeyan, S. (International Union of Crystallography, 2014)
In the title compound, C(11)H(10)O(4), the methyl acrylate substituent adopts an extended E conformation with all torsion angles close to 180°. The conformation of the keto group with respect to the olefinic double bond is typically S-trans. In the crystal, molecules are linked via pairs of C—H⋯O hydrogen bonds, forming inversion dimers with an R (2) (2)(8) graph-set motif. The dimers are further linked via C—H⋯O hydrogen bonds, forming chains along [001], which enclose R (3) (2)(16) graph-set ring motifs. The keto group O atomaccepts two C—H⋯O interactions.